The first information report and other non first information reports distinguished - Mohamed Zaman Ramzan Din, (Fakulti Undang - Undang, 2006)

(untitled)
This article discusses the importance of the first information report. The relevant provision is found in section 107 CPC of Part 5 Chapter 12 of Criminal Procedure Code. This is the basis upon which an investigation under this chapter commences. The object of the first information report is to make a complaint to the police so as to set the criminal law in motion. The value of such first information report is that it is the first report of an occurrence to the police and as such is entitled to the most careful consideration by the courts of law. Its importance lies in the fact that it is presumed to be untutored, unplanned and unthought out version of the incident just as it reaches the police. It is therefore obvious that the object of the first information report is to enable the courts to have the information about a crime given before it could be developed or embellished in any manner. It follows that any statement recorded after the commencement of the investigation and after there has been some development, has little or no value at all as first information because it can be made to fit into the case as developed. Another category is non first information reports. At the moment all these appear to be lumped into section 107 Criminal Procedure Code and these non FIR remains. Must there be a formal police report lodged before criminal investigation first information report commences? Whether the police could on their own initiative base on information received from their own sources start the investigation? This article surveys this aspect too. Finally, in the context of admissibility, what really is the value of such first information report and whether it carries any corroborative impact during trial? This is analysed by looking at the relevant provision in the Evidence Act 1950